Assessing the Impact of Maqasid Shariah on National Happiness Index: An Empirical Simulation in the Indonesian Context - Isnaini Harahap; Marliyah Marliyah; Chuzaimah Batubara; Khairina Tambunan; Early Ridho Kismawadi (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2026)
Happiness (falah) constitutes the ultimate objective of Islamic economics, encompassing both material prosperity and spiritual well-being within the framework of Maqāṣid al-Sharī‘ah. However, conventional welfare indicators—such as GDP and income—remain limited in capturing the moral, psychological, and social dimensions of human well-being. This study aims to empirically examine the contribution of the five dimensions of Maqāṣid al-Sharī‘ah—preservation of religion (ḥifẓ al-dīn), intellect (ḥifẓ al-‘aql), life (ḥifẓ al-nafs), progeny (ḥifẓ al-nasl), and wealth (ḥifẓ al-māl)—to Indonesia’s National Happiness Index. Using balanced provincial panel data covering 34 provinces across three observation periods (2014, 2017, and 2021), this research applies a Fixed Effects panel regression model, selected based on Chow and Hausman tests, to estimate the impact of each dimension. The findings indicate that ḥifẓ al-nafs (proxied by labor force participation) and ḥifẓ al-nasl (life expectancy) exert statistically significant but negative effects on happiness. In contrast, ḥifẓ al-dīn (zakat), ḥifẓ al-‘aql (literacy rate), and ḥifẓ al-māl (GRDP per capita) show positive but statistically insignificant relationships. These results suggest the presence of non-material trade-offs, where increased economic participation and demographic improvements do not necessarily translate into higher subjective well-being. The study provides empirical support for the argument that national happiness cannot be adequately explained by economic growth alone. Instead, it requires a multidimensional framework that integrates spiritual, social, and ethical dimensions, as emphasized in Islamic welfare theory. This research contributes to the literature by bridging Maqāṣid al-Sharī‘ah with empirical happiness measurement and offers policy implications for designing more holistic and value-based development indicators in Muslim-majority contexts.